2019
DOI: 10.1371/journal.pone.0225612
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and mortality in old and very old patients undergoing cardiac resynchronization therapy

Abstract: AimCardiac resynchronization therapy (CRT) is a valid therapeutic option for patients with heart failure (HF). However, the elderly population was not well represented in the guidelines. The primary end point was to evaluate the impact of advanced age on clinical response and cardiovascular and total mortality of patients undergoing CRT. The secondary end point was to assess the rate of acute complications related to the procedure. Methods and resultsA total of 249 consecutive patients with HF and optimized tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(40 reference statements)
1
3
0
5
Order By: Relevance
“…A gyógyszeres kezelést illetően, változó arányban alkalmazták a szívelégtelenség bázisterápi áját képező gyógyszereket az idősebb korosztályban. Ezen felül jellemzően kisebb arányban implantáltak CRTDkészüléket idős betegek esetében (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Kiindulási Klinikai Paraméterekunclassified
See 3 more Smart Citations
“…A gyógyszeres kezelést illetően, változó arányban alkalmazták a szívelégtelenség bázisterápi áját képező gyógyszereket az idősebb korosztályban. Ezen felül jellemzően kisebb arányban implantáltak CRTDkészüléket idős betegek esetében (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Kiindulási Klinikai Paraméterekunclassified
“…Vizsgálatukban multivariáns Cox regressziós analízissel a 80 évnél idősebb életkor, a krónikus obstruktív tüdőbetegség és a krónikus vese betegség mutatott összefüggést a halálozással. Hason ló eredményeket írtak le Montenegro és munkatársai is, azonban ebben a vizsgálatban a kardiovaszkuláris mortalitást külön is vizsgálva azt találták, hogy annak gyakorisága független az életkortól (22). Fumagalli és munkatársai analízisében ezzel ellentétben a 75 évnél idősebbek mortalitási aránya csak a 65 évnél fiatalab bakhoz képest volt szignifikánsan magasabb, a 65-74 évesekkel azonban összevethető volt a halálozási rá tájuk (21).…”
Section: Crt-re Adott Klinikai Válasz éS Prognózisunclassified
See 2 more Smart Citations
“…In fact, the relationship between sex, race, and age and CRT patient outcomes has produced mixed study results. Although some studies have reported that there is no difference in clinical cardiovascular (CV) outcomes and mortality based on race 9 and age, 10 , 11 , 12 others suggest that CRT produces notable differences between these populations. Specifically, women may have greater reduction in all-cause death and worsening HF after CRT intervention.…”
mentioning
confidence: 99%